Determination of Contact Stiffness and Damping of a Tie-Bolt Rotor with Interference Fits Using Model Updating with Thin-Layer Elements - Pu Li; Qi Yuan (Shock and Vibration)
Tie-bolt rotors are commonly applied in aeroengines and gas turbines, and interference fits ensure accurate positioning for disk assembling. This paper presents experimental and numerical studies on the stiffness and damping properties of a tie-bolt rotor with interference fits under different preloads. An FE model incorporating thin-layer elements is used to carry out model updating to predict the contact stiffness and damping characteristics. A two-step model updating approach of the tie-bolt rotor using the response surface optimization is implemented. Finally, a quasistatic FE simulation concerning the interference fits and sensitivity analysis is performed to validate the experimental results. Press fit induces a bilinear contact stiffness. Also, modal damping demonstrates a more sensitive and nonmonotonic behavior versus preload.